2004
DOI: 10.1111/j.1365-2133.2004.05563.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma trough levels of mycophenolic acid do not correlate with efficacy and safety of mycophenolate mofetil in psoriasis

Abstract: The monitoring of MPA trough levels with EMIT appears to be a poor predictor of efficacy or toxicity. In contrast, it is a useful tool to evaluate the degree of therapeutic compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Mycophenolic acid reversibly blocks the de novo synthesis of guanine nucleotides and thus preferentially affects both B and T lymphocytes 18 . Numerous reports have described the utility of MMF for the treatment of psoriasis with promising results 9–12 . The effectiveness of MMF in our study is in agreement with those of earlier studies 9–12 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mycophenolic acid reversibly blocks the de novo synthesis of guanine nucleotides and thus preferentially affects both B and T lymphocytes 18 . Numerous reports have described the utility of MMF for the treatment of psoriasis with promising results 9–12 . The effectiveness of MMF in our study is in agreement with those of earlier studies 9–12 .…”
Section: Discussionsupporting
confidence: 89%
“…It is the pro‐drug of mycophenolic acid, which was originally used to treat psoriasis in the 1970s but was associated with a relatively high incidence of gastrointestinal and infectious adverse effects 5,6 . Although there are no double‐blind randomized trials of MMF in the treatment of psoriasis, it has been used in several uncontrolled studies 7–10 . An open‐label study of 23 patients with moderate to severe psoriasis demonstrated a mean PASI reduction of 47% at 12 weeks of therapy when dosed at 2 to 3 g daily, 11 whereas another smaller open‐label study of four patients demonstrated a 62.5–90% reduction in PASI after 3 months of therapy (2 g/day) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The patient's Psoriasis Area and Severity Index (PASI) score decreased from 22.0 to 11.4 over 5 weeks. 15 Numerous reports since have described the utility of MMF in treating psoriasis as either monotherapy or adjuvant therapy with promising results [16][17][18][19][20] (Table II). Two of these studies reported a 75% reduction in PASI in at least 50% of subjects.…”
Section: Psoriasismentioning
confidence: 97%
“…The normal dose of EC-MPS (1440 mg daily) appeared to be more effective than the low dose, because the psoriasis worsened in several patients after dose reduction. Some case reports and small series of patients have reported the efficacy of MMF in the treatment of moderateto-severe psoriasis (8)(9)(10)(11)(12)(13)(14). At usual doses, MMF is generally well tolerated.…”
Section: Discussionmentioning
confidence: 95%